Diagnostic accuracy of DW MR imaging in the differentiation of chordomas and chondrosarcomas of the skull base: A 3.0-T MRI study of 105 cases - Welzel, Thomas; Meyerhof, Eva; Uhl, Matthias; Huang, Kristin; Deimling, Andreas von; Herfarth, Klaus; Debus, Jürgen (European journal of radiology, 2018)
Purpose - To determine the diagnostic accuracy of DW MR imaging with apparent diffusion coefficient (ADC) mapping for the distinction of skull base chordoma from skull base chondrosarcoma. - Patients and Methods - From October 2009 to April 2014, 105 consecutive patients (chordomas (n=70), and chondrosarcomas (n=35) who were planned to receive proton or heavy-ion beam therapy underwent DW MR imaging on a 3.0T. MR images were assessed by means of consensus of three experienced radiologists who were blinded to pathologic and clinical information. ADC values (mean, minimum, maximum, and normalized) of the solid tumor component were evaluated. Group means and cut-off points were established to separate skull base chordoma from skull base chondrosarcoma, and statistical significances were calculated by Student’s t or Mann-Whitney-U tests, and receiver operating characteristic (ROC) curve analyses. The prospective study was approved by the institutional ethics committee. - Results - For solid tumor component, there were higher mean, minimum, maximum, and normalized ADC values in chondrosarcomas compared with those in chordomas (all p<0.001). ROC analysis revealed areas under the curve for mean, minimum, maximum, and normalized ADC values between 0.79 and 0.93. The mean ADC value of the solid tumor components had the best AUC, with a cut-off point of 1585×10(−6) mm (2)/s and sensitivity and specificity of 94.3% and 98.6%, respectively. - Conclusion - Skull base Chondrosarcomas generally have higher mean, minimum, maximum, and normalized ADC values than skull base chordomas, with the mean ADC value of the solid tumor component offering the highest accuracy for characterization.
Gesehen am 12.03.2020